P1-S1.53 Assessing HPV genotype prevalence in Australian women by Indigenous ethnicity pre-vaccination. (10th July 2011) - Garland, S M; Brotherton, J M L; Stevens, M I; Tabrizi, S N I; Condon, J; McIntyre, P; Smith, D
Abstract : Background: A government funded HPV vaccination program was implemented across Australia from April 2007. The aim of this study was to ascertain whether HPV genotype prevalence, prior to vaccination, differed significantly by Indigenous status, age group, Pap cytology status or area of residence. Methods: We used women attending for routine Pap smear, (April 2005–February 2008), as the sampling frame with 34 sites across Australia selected to include adequate numbers of Indigenous and remote-dwelling women. The final recruitment of 2620 (mean 33, range 15–66 years) included 26% (684) indigenous. DNA extracts from Thin-Prep specimens were screened by HPV AMPLICOR (Roche) and in-house HPV PCR/ELISA, with positives genotyped by LINEAR ARRAY HPV genotyping test (Roche). Results: The overall prevalence of HPV infection was 39% (95% CI—36.8 to 40.6), with high risk (HR) HPV detected in 26% (95% CI—24.8 to 28.2). Single infections were detected in 17% (95% CI—15.8 to 18.7). While multiple infections were common overall at 22%, there was no difference in proportion of multiple HPV carriage between indigenous and non-indigenous (58% of HPV positive non-Indigenous women and 56% of HPV positive Indigenous women had multiple types detected). As with single infections, multiple type infections were less prevalent with increasing age. The six most common genotypes were—HPV 16 (8.3%), 51 (5.1%), 53 (4.7%), 62 (4.3%), 89 (3.9%) and 52 (3.8%). Age-specific HPV prevalence rates were similar for Indigenous and non-Indigenous women aged ≤30, but higher for Indigenous women aged 31–40, particularly for non-vaccine targeted HR-HPV genotypes. By HPV clades for this age group, indigenous women were significantly more likely to have α 7 HPV ((45, 39, 59, 68 or 70 without 18) OR 1.9 (1.1 to 3.3) p=0.03) or α 5 group (HPV51, 26, 69, 82) with OR 2.1 (1.1 to 4.3) p=0.02). There was no significant association between Indigenous status and detection of HPV from the α 9 clade (31, 33, 35, 52, 58, 67), with or without HPV 16. Overall, HR-HPV prevalence increased from 21% in women with normal cytology, to 81% in those with high-grade lesions/cancer. Conclusions: Cross-sectional prevalence of HR-HPV was high in Australian women, with vaccine preventable genotypes observed in 13% of all women (25% in <25 year olds). Vaccination should significantly reduce vaccine related HPV infection and disease in Australian women, irrespective of indigenous status or area of residence.